Influence Operating Cash Flow , Capital Intensity , and Sales Growth Against Company Value - Ummaro Nur'Azizah; Ita Darsita (EkoPreneur, 2025)
This study aims to analyze the effect of Operating Cash Flow, Capital Intensity, andSales Growth on Firm Value. This study was conducted by analyzing the financialstatements of companies in the Consumer Non-Cyclical sector listed on theIndonesia Stock Exchange (IDX) during the period 2019 to 2023. The sample usedin this study was 33 Consumer Non-Cyclical sector companies listed on theIndonesia Stock Exchange (IDX) during the period 2019 to 2023 using a purposivesampling technique. The data used in this study are secondary data in the form offinancial statements from each company that has been used as a research sample.The variables used in this study are Operating Cash Flow (X1) as the firstindependent variable, Capital Intensity (X2) as the second independent variable,and Sales Growth as the third independent variable, and Firm Value (Y) as thedependent variable. The panel data regression method is used as the researchmethodology in this study. The analysis of the results of this study uses the help ofEviews 12 Student Version Lite software. The results of this study indicate that thebest model is the Random Effect Model (REM). The results of this study indicatethat Operating Cash Flow partially has no effect on Company Value, CapitalIntensity partially affects Company Value, and Sales Growth partially affectsCompany Value. Simultaneously, Operating Cash Flow, Capital Intensity, and SalesGrowth affect Company Value.   Keywords: Operating Cash Flow; Capital Intensity; Sales Growth; CompanyValue.